Physical investigations on undoped and Fluorine doped SnO2 nanofilms on flexible substrate along with wettability and photocatalytic activity tests. (April 2017) - Ameur, S. Ben; Barhoumi, A.; Bel hadjltaief, H.; Mimouni, R.; Duponchel, B.; Leroy, G.; Amlouk, M.; Guermazi, H.
Abstract: A successful deposition of undoped and Fluorine doped tin oxide (TO and FTO) nano films at relatively low temperature 250 °C on flexible substrate (Polyethyerimide) was obtained using the spray pyrolysis technique. The Fluorine doping effects on the structural, morphological and optical properties were investigated. XRD measurements permit textural characterization, and show that the films have a tetragonal polycrystalline structure. The increase of crystalline size and reduction of defects and strain with Fluorine doping improve the crystalline quality. This is may be due to the substitution of O −2 by F - . Furthermore, the structural changes of the films affected the surface roughness which became rough with the Fluorine. This was confirmed by wettability measurements. Moreover, the gap energy exhibits a slight red-shift with F-doping. The photoluminescence spectra showed that Fluorine doping increased the radiative centers, which is confirmed by structural results. The photocatalytic performance of TO and FTO nanofilms were investigated by degradation of crystal violet dye under UV radiations. Results showed that TO and FTO exhibit high photocatalytic activities, which can be enhanced by H2 O2 addition.